Research Note: Total Free Sulphydryls of Several White and Red Wines - Kontogeorgos, N.; Roussis, I.G. (South African Journal of Enology and Viticulture, 2016)
Total free sulphydryl groups were assessed in several white and red wines. Ellman’s method was adapted to wine samples for the determination of total –SH groups. Total –SH groups of white wines, as glutathione, were in the range of 315 to 734 and of red wines in the range of 163 to 467 mg/L. In most cases, white wines exhibited higher values than red wines. The high total sulphydryls of white and red wines indicate their potential contribution to wine antioxidant capacity.